Nutraceuticals : efficacy, safety and toxicity - Gupta, Ramesh C. (Ramesh Chandra), 1949-; Lall, Rajiv; Srivastava, Ajay (Academic Press, 2021)
Nutraceuticals: Efficacy, Safety and Toxicity, Second Edition, brings together everything that is currently known about nutraceuticals and their potential toxic effects. The book introduces readers to nutraceuticals, herbal medicines, Ayurvedic medicines, prebiotics, probiotics, adaptogens, and their uses and specific applications. This essential reference discusses the mechanism of action for the judicious use of these nutraceuticals and the best tools for their evaluation before detailing the safety and toxicity of nutraceuticals and interactions with other therapeutic drugs. Finally, and crucially, regulatory aspects from around the world are covered. Completely revised and updated, this updated edition provides toxicologists, pharmacologists, pharmaceutical scientists, and those interested in medicinal plants and natural products with a comprehensive overview of the most effective tools upon which to evaluate the safety and toxicity of nutraceuticals, prebiotics, probiotics and alternative medicines.